THỰC TRẠNG VÀ GIẢI PHÁP CHO SỰ LIÊN KẾT ?BỐN NHÀ? TRONG SẢN XUẤT VÀ TIÊU THỤ NÔNG SẢN Ở ĐỒNG BẰNG SÔNG CỬU LONG - Hiếu, Trần Văn (Tạp chí Khoa học Đại học Cần Thơ, 2004)
Integrating ?Four factors? (State ? household ?Entrepreneur ? Scientist) is one of the major solutions that contribute effectively in the process of producing and consuming argri- produce in Mékong Delta at present. In recent years, in Mékong Delta, some effective linking ?four factors? patterns have appeared, such as: Sông Hậu Farm, Cần Thơ Mékong Company, An Giang Antesco Company v.v...  However, the above patterns are small in number and untight.  In general, we have not created a mechanism to combine ?four factors? together.